(untitled) (Clinics, 2015)
OBJECTIVES: Septic pulmonary embolism caused by a Klebsiella (K.) pneumoniae liver abscess is rare but can cause considerable morbidity and mortality. However, clinical information regarding this condition is limited. This study was conducted to elucidate the full disease spectrum to improve its diagnosis and treatment. METHOD: We reviewed the clinical characteristics, imaging findings, and clinical courses of 14 patients diagnosed with septic pulmonary embolism caused by a K. pneumoniae liver abscess over a period of 9 years. RESULTS: The two most prevalent symptoms were fever and shortness of breath. Computed tomography findings included a feeding vessel sign (79%), nodules with or without cavities (79%), pleural effusions (71%), peripheral wedge-shaped opacities (64%), patchy ground-glass opacities (50%), air bronchograms within a nodule (36%), consolidations (21%), halo signs (14%), and lung abscesses (14%). Nine (64%) of the patients developed severe complications and required intensive care. According to follow-up chest radiography, the infiltrates and consolidations were resolved within two weeks, and the nodular opacities were resolved within one month. Two (14%) patients died of septic shock; one patient had metastatic meningitis, and the other had metastatic pericarditis. CONCLUSION: The clinical presentations ranged from insidious illness with fever and respiratory symptoms to respiratory failure and septic shock. A broad spectrum of imaging findings, ranging from nodules to multiple consolidations, was detected. Septic pulmonary embolism caused by a K. pneumoniae liver abscess combined with the metastatic infection of other vital organs confers a poor prognosis.